Are state-owned firms less profitable than non-state-owned firms? European evidence - Gaio, Cristina (2016)
Prior research suggests that state-owned enterprises (SOE) have lower performance levels than non-state-owned enterprises (NSOE). The main goal of this study is to analyse the impact of State ownership on profitability, using two major measures of performance: Return on Equity and Return on Assets, and a broader sample of about 11,000 firms, from 37 countries, between 2003 and 2011. Our main results suggest that SOE are less profitable than NSOE for both performance measures. This finding remains equal in the crisis periods and for Western and Eastern Europe countries. We also find a negative relationship between State control and SOE´s profitability levels. Additional results indicate that, in general, SOE from Western Europe are more profitable than SOE from Eastern Europe.